Pengaruh Intensitas Hujan Terhadap Kecepatan dan Tinggi Banjir Lahar Berdasar Permodelan SIMLAR 2.1 - Rokhmat Hidayat; Akhyar Musthofa; Pedri Bahri (JURNAL TEKNIK HIDRAULIK, 2017)
Large amount of active volcanoes distribution makes Indonesia a country vulnerable to lahar flow. Although lahar flow is categorized under volcanic eruption secondary disaster, it has large impacts in environmental, social, economic, infrastructure and casualties. For example, the incident of lahar flow disaster triggered by high rainfall was occurred in Putih River Magelang, on 24th January 201 . This study discusses the effect of rainfall intensity on lahar flow velocity and height. This study was carried out using a numerical model, SIMLAR 2.1, in Putih River, located on western slopes of Merapi Volcano, Magelang, Central Java. Modeling was performed by using several rain intensity scenarios, i.e. 60mm/hour, 70mm/hour, 80mm/hour, 90mm/hour and 100mm/hour. The velocity of lahar flow simulated by the model was validated using lahar flow velocity data from field measurement. The results showed that rainfall intensity has linear correlation with lahar flow velocity and height. Higher rainfall intensity results in higher lahar flow velocity and height. In addition, the modelling result also showed that the largest lahar flow velocity (2,88m/s) occurred when the rainfall was 100mm/hour and has a deviation of 17.71% compared to previous observations. In average, lahar height in the River increases around 24.31% when the rainfall increases 10 mm/hour.